Penerapan Revenue Sharing Contract Pada Klaster Industri - Nurwidiana, Nurwidiana (Department Industrial Engineering, University of Muhammadiyah Malang, 2012)
Industry cluster are geographic concentrations of competing, complementary, or interdependent firm and industriesÂ that do business with each other and/or have common needs for talent, technology, and infrastructure. In a industry cluster,Â the relationship should be profitable for each other. However, in the absence of contract, Small Medium Enterprises (SMEs)Â as producers, do not have a strong bargaining position compared to a distributor as supporting industry so that SMEs are frequently lost. This research focus on the revenue sharing contract as an effort of coordination in snacks industry cluster. In the revenue sharing contract the manufacturer charges the distributor a low price and shares a fraction f of revenue generates by distributor. Based on the analysis has been performed, implementing revenue sharing model, can reduce the overstock cost so that it can increase the quantity orders from distributors and finally increase profits for both the SMEs and distributor. In order to gain optimum profit, it is needed to set the fraction (f) of profit sharing on revenue sharing contract. The implementation of this model requires information sharing between the SMEs and distributor.